Abstract determinations and conceptual notion of education. A critical reading of the accumulation of knowledge (Revista ABRA, 2017)
From a long-term historical perspective, some conceptual determinations regarding education are presented identifying seven core educational moments in mankind. This overview includes history starting from the appearance of the modern human in about 130000 BC until the formalization of human knowledge, which was typical of the Hellenistic tradition during the 6th and 3rd centuries BC. The Hellenocentric point of view influencing educational dynamics and logic is confronted to promote discussion beyond this point of view. The paper is aimed at identifying the intellectual and material conditions that allow producing and reproducing life on the only planet in the Milky Way where life is possible.